The Practice of Introducing Category Management Methodology in Internet-Shop (Illustrated by the Ural Federal District) - K. M. Ilyenkova (Plekhanov Russian University of Economics, 2019)
In view of global changes that took place in the last decade in consumer behavior, competition rate and economy in general conditions of doing business are changing. Trade organizations have to search for new ways of raising efficiency in their economic activity. The article analyzes the fast growing internet-trade market. It studies the practice of introducing category management methodology in the internetshop, which works on pets’ goods market of the Ural federal district. During the research the following methods were used: system approach, comparative analysis, synthesis, economic modeling, as well as empiric and expert-analytical and statistic methods of economic analysis. The author prepared recommendations aimed at improvement of product range policy and demonstrated a great potential of the internet-shop, which could help develop strategy and tactics of product sub-categories being analyzed and forecast planned economic indicators. The present research is important for Russian trade companies, especially of the regional level. The author came to the conclusion that in case of adequate planning and product range management category management would provide an opportunity to improve economic figures of the company. Competitiveness of the company could be raised at the expense of meeting customers’ needs taking into account their requests and expectations.